The Consequences of Drug-drug Reactions Impose Limits on Formulating a Cure for Alzheimer’s Dementia - Fessel, Jeffrey (Archives of Clinical and Biomedical Research, 2025)
This article uses the example of drugs that might cure Alzheimer’s dementia in order to illustrate that consequences of undesirable drugdrug interactions may limit the treatment that may be safely used for any medical condition. As many as 18 elements may participate in the cause of AD, and their suppression may require choosing from 24 individual drugs. That number of drugs may be greatly reduced by excluding those that cause undesirable consequences from drug-drug interactions between the two drugs in each pair. Also, there is a limit to the number of drugs that is tolerable, especially in the elderly who have other conditions requiring drugs. In fact, meaningful simplification of therapy intended to cure a problem such as AD, that has several contributing components, can often be achieved only if there are proxies for those components. In that regard, the present article is intended to make the task easier by providing just two proxies, i.e., dopamine (DA), and serotonin (5-HT), for the 24 drugs that might potentially cure AD. Levels of DA and 5-HT are decreased in AD and each of them has critical importance for brain function, so raising their levels stands a good chance to cure AD. After excluding from the 24 drugs, those pairs of drugs that produce undesirable effects from consequences of drug-drug interactions, only nine drugs remain that may be safely used.